A wireless ECG sensor and a low-complexity screening algorithm for obstructive sleep apnea detection - Wong, Kiing (IEEE xplorer, 2012)
Obstructive sleep apnea (OSA) is a disease that is related to inability of a person to sleep properly and often the characteristics is diagnosed in sleep laboratory using method called as polysomnography. In the traditional method of polysomonogrphy monitoring, an OSA patient is required to be hospitalized and several vital signs are taken from the patient, including electroencephalography (EEG), photoplethysmography (PPG) and electrocardiography (ECG). This method has brought up a lot of problems such as high cost, discomfort to patients and inaccuracies of OSA analysis. This paper introduces a current method of polysomnography that requires ECG data alone. A patch-type ECG sensor was designed, and its features a low-cost, small size, and wireless electronic device. Therefore, the patient is allowed to be monitored away from the hospital. An ECG screening algorithm is developed based on a FIR filter and a fast Walsh-Hadamard Transform in Matlab software environment. The screening algorithm is used to allow both healthcare service providers and medical specialists to monitor and verify the patient's OSA conditions.